Pharmacokinetics, Pharmacodynamics, and Safety of ASP015K (Peficitinib), a New Janus Kinase Inhibitor, in Healthy Subjects. Issue 6 (30th June 2016) - Cao, Ying Jun; Sawamoto, Taiji; Valluri, Udaya; Cho, Kathy; Lewand, Michaelene; Swan, Suzanne; Lasseter, Kenneth; Matson, Mark; Holman, John; Keirns, James; Zhu, Tong
Abstract: Two randomized, double‐blind, placebo‐controlled studies are reported that had the objective to evaluate the pharmacokinetics, pharmacodynamics, and safety of ASP015K (peficitinib), a Janus kinase (JAK) inhibitor, in healthy subjects. The single‐dose study included 7 male groups (3–300 mg) and 2 female groups (30 or 200 mg), n = 8/group (6 on ASP015K and 2 on placebo in each group). The multiple‐dose study included 1 female and 3 male groups, n = 12/group (9 on ASP015K and 3 on placebo in each group), who received ASP015K (30 mg) or placebo every 12 hours (twice a day) for 14 days. In the single‐dose study, plasma ASP015K concentration increased dose‐proportionally. Food increased ASP015K exposure (AUCinf ) by 27%. Mean peak JAK inhibition increased with dose, from 6% at 4 hours (median) following ASP015K 3 mg to 93% (range, 89%–98%) at 2 hours (median) after ASP015K 300 mg. In the multiple‐dose study, ASP015K plasma exposure reached steady state by day 3. On day 14, mean ASP015K peak concentration was 38%–65% higher than after the first dose; peak JAK inhibition following 100 or 200 mg twice daily was >85%. The most common adverse events (AEs) were neutropenia, headache, and abdominal pain; no serious AEs occurred. The safety findings at pharmacologically effective doses of ASP015K support further clinical development.